Leucine Supplementation Did Not Improve Protein Deposition or Lysine Utilization in Growing Steers - K. A. Pearl; H. F. Speer; M. D. Miesner; E. C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:This study was conducted to determine if leucine supplementation could improve protein deposition and lysine utilization in growing steers. Study Description:Ruminally cannulated Holstein steers (380 lb) were provided treatments of postruminal infusions of 0 or 0.212 oz/day of lysine, and 0, 0.529, or 1.058 oz/day of leucine, with all 6 combinations tested. Ruminal infusions of volatile fatty acids and abomasal infusions of glucose provided energy, and all essential amino acids, except lysine, were infused abomasally to make lysine the sole limiting amino acid. Urine and fecal collections were used to measure nitrogen retention (protein deposition). The Bottom Line:Supplementation with leucine did not affect protein deposition of growing steers when lysine was a limiting amino acid, suggesting that, at the levels included in this study, leucine did not stimulate protein synthesis.
Keywords: leucine; lysine; steer